Evaluating Handover Processes in Mobile Networks: Effects on Latency, QoS, and User Experience Across Conditions - Abdurrahman, Mubarak; Gamawa, Mansur Aliyu; Abdulkadir, Abubakar; M, Bala A.; Hamza, Jamilu Bala; Ahmed, Abubakar (Darul Yasin Al Sys, 2025)
The rapid expansion of mobile networks has revolutionized global communication, enabling seamless connectivity for a growing user base. As networks evolve, efficient handover processes—where mobile devices transition between network cells or base stations—are critical to maintaining uninterrupted service. Poorly optimized handovers can result in increased latency, degraded Quality of Service (QoS), and diminished user experience, especially in advanced networks like 5G that demand low latency and high reliability. This study examines the impact of handover processes on key performance metrics such as latency, QoS, and user satisfaction, analyzing their behavior across urban, rural, and heterogeneous technological environments. In densely populated urban areas, frequent handovers risk creating performance bottlenecks, while rural areas face challenges related to sparse infrastructure. Heterogeneous environments, where legacy and next-generation technologies coexist, further complicate efficient transitions. By identifying these challenges, the study proposes strategies to optimize handover efficiency, ensuring seamless connectivity, enhanced QoS, and reduced latency in advanced networks. These findings contribute to improving mobile communication systems, addressing the dynamic demands of 5G and beyond in diverse operational scenarios.